Multi-cloud-aware middleware - SILVA, Tércio de Morais Sampaio (2021)
The idea of collaboration among clouds has emerged to address issues related to single cloud adoption. From the developer’s perspective, distributed applications can take advantage of multi-cloud environments to create, extend and integrate their components across cloud domains in a dynamic, automatic and transparent way and improve their quality requirements, such as availability, performance, and scalability. However, the management complexity increases sub- stantially in this scenario, whose responsibility lies with the developer. Despite standardisation efforts, most applications cannot exploit multi-cloud benefits (e.g., elasticity). Furthermore, solutions for interoperability, cloud’s administrative boundaries, and the lock-in problem remain as open challenges, concerning at the IaaS level, unaware of what is running on top of it. This work proposes a middleware architecture for distributed applications in multi-cloud environ- ments: Multi-Cloud Aware Middleware (M-CaMid). The architecture combines middleware functionalities with IaaS services for distributed application management. M-CaMid takes ad- vantage of elasticity to provide a cross management that integrates infrastructure and application layers (vertical management) and integrate many clouds (horizontal management), enabling a holistic view of distributed systems and a better application performance and rational usage of cloud resources. Experiments were carried out to assess the performance gains due to M-CaMid. Results show that cross management can improve performance of distributed applications and ra- tional usage of cloud resources for distributed applications in a multi-cloud environment. Thesis’ unique contributions are: (i) middleware architecture for distributed application management in a multi-cloud environment; (ii) cross management that integrates infrastructure and application layers and many clouds; and (iii) multi-cloud elasticity that extends single cloud elasticity to the multi-cloud scope.